Energy management strategy for electric vehicles with hybrid storage system using economic predictive control (MASKAY, 2019)
This work proposes economic predictive control as a technique for optimum energy management of a hybrid vehicle. The model used for the control is described, and an economic predictive controller is designed from it. Finally, the best adjustment of the controller weights that achieves the most significant reduction in fuel cell consumption with the help of batteries and supercapacitors is studied. For this purpose, the fuel cell's maximum and minimum consumption points are determined, and the multiobjective control problem is characterized by determining the Pareto curves. The article concludes with a discussion of the results and future work.
Keywords: Economic predictive control; hybrid vehicles; fuel cell; batteries; supercapacitors; multi-objective control